IDENTIFIKASI KEJADIAN LASERASI PERINEUM SAAT PERSALINAN DI PMB NGUDI SARAS, JATEN, KARANGANYAR TAHUN 2021 - Suwarnisih Suwarnisih (Sekolah Tinggi Ilmu Kesehatan Mitra Husada Karanganyar, 2022)
ABSTRACT One indicator of a nation's health status is AKI (Maternal Mortality Rate) and IMR (Infant Mortality Rate). MMR and IMR are still a big problem for the Indonesian people so that maternal and child health services are a top priority in health development in Indonesia. The focus of normal delivery care is clean and safe delivery and prevent complications (PP IBI, 2016). Spontaneous perineal tear is a tear in the space in the form of a parallelogram located below the pelvic floor that occurs naturally without any action during delivery. The purpose of this study was to determine the incidence of perineal laceration during delivery at PMB Ngudi Saras Jaten, Karanganyar. Descriptive observational research method. The population in this study was 72 people the sampling technique used was